Affordability of the EAT–Lancet reference diet: A global analysis - Hirvonen, Kalle; Bai, Yan; Headey, Derek D.; Masters, William A. (Elsevier, 2020)
The EAT–Lancet Commission drew on all available nutritional and environmental evidence to construct the first global benchmark diet capable of sustaining health and protecting the planet, but it did not assess dietary affordability. We used food price and household income data to estimate affordability of EAT–Lancet benchmark diets, as a first step to guiding interventions to improve diets around the world.